2016
DOI: 10.1063/1.4965572
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and impact modification of polypropylene laser sintered parts

Abstract: Abstract. Selective laser sintering (SLS) is a manufacturing technology whereby parts are built through layerwise application and selective consolidation of a polymer powder by a laser. With this additive manufacturing technology, polymer parts can be built with nearly no limits to complexity and nearly without geometrical constraints. Recently, a handful of polypropylene (PP) materials has been added to the rather limited portfolio of laser sintering powders. In conventional extrusion, the use of nucleating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…[ 12,15 ] However, the use of nanoparticles can negatively affect the processability of the polymer powders, as they can also act as heterogeneous nuclei for polymer crystals, thus accelerating the crystallization kinetics [ 16 ] and narrowing the thermal process window. [ 17 ] Hence, only small amounts of flowing agents in the range of 0.1 wt% are typically used. [ 12,18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 12,15 ] However, the use of nanoparticles can negatively affect the processability of the polymer powders, as they can also act as heterogeneous nuclei for polymer crystals, thus accelerating the crystallization kinetics [ 16 ] and narrowing the thermal process window. [ 17 ] Hence, only small amounts of flowing agents in the range of 0.1 wt% are typically used. [ 12,18 ]…”
Section: Introductionmentioning
confidence: 99%
“…* The values were not provided directly, and they have been interpreted from experimental data. [24,25,31,32,34]. …”
Section: Figurementioning
confidence: 99%
“…PP is already widely used in FMCGs on account of its low cost, good chemical resistance, and reasonably robust mechanical properties. Furthermore, PP has already been shown to useful in LS, with several studies reporting the manufacture of good quality PP parts by LS (Wegner, 2016;Drummer et al, 2010;Zhu et al, 2015;Kleijnen et al, 2016;Ituarte et al, 2018), although the exact part properties are dependent on the specific grade of PP powder used. For example, early research by Drummer et al demonstrated that while they could produce PP parts by LS, the mechanical properties obtained were significantly lower than both comparable PA12 parts, and benchmark values for injection molded PP (Drummer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%